Optimalisasi Peran Guru dan Orang Tua dalam Menangani Gangguan Artikulasi Anak Usia Dini 5-6 Tahun - Dina, Arina Rafa; Andini, Astiyah; Sihombing, Yolanda Agustina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this study was to determine the articulation disorders experienced by children as an early detection step carried out by teachers to be consulted directly with a psychologist or child development therapist. The method used in this study is a qualitative method with a case study approach. The study was conducted at Petro Kindergarten. The subjects were 2 children aged 5-6 years and 1 class teacher at Petro Kindergarten and 2 parents of the children. The results of observations at Petro Kindergarten were carried out by researchers to observe how teachers, parents, and health workers deal with problems related to language development disorders, namely by spontaneously improving words or sentences in children who experience these disorders. Early intervention and the right approach in education and learning at home are important steps in supporting children's language development.